The Effect of Differences in Mocaf Starch Weight and Glycerol Percentage on the Physical and Mechanical Properties of Bioplastics - Wijayanti, Ruri; Kasim, Anwar; Emriadi, Emriadi; Rozen, Nalwida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The present study aims to analyse the effect of variations in the amount of Mocaf starch and glycerol concentration on the physical and mechanical characteristics of the bioplastics produced. The method employed in this study was casting. The experimental design employed in this study was a completely randomised two-factor design, namely the amount of starch (4, 5, 6 and 7 g) and glycerol concentration (20, 30, and 40% w/w based on starch). The data were analysed using analysis of variance (ANOVA) at a significance level of 5%; when significant differences were identified, Duncan's test was used to follow up. The findings indicated that the quantity of mocaf starch and glycerol concentration exerted a substantial influence on the physical and mechanical properties of bioplastics. An increase in the amount of starch led to an increase in density, thickness, and, most significantly, tensile strength. Conversely, an increase in glycerol concentration did not affect the density, but increased the thickness and elongation, while decreased the tensile strength. The interaction of these two factors also had a significant effect on thickness, tensile strength, and elongation. Contribution to Sustainable Development Goals (SDGs):SDG 12 – Responsible Consumption and Production (Renewable-based bioplastics, sustainable materials)SDG 9 – Industry, Innovation, and Infrastructure (Innovation in biodegradable materials)SDG 13 – Climate Action (Reduction of fossil-based plastics)SDG 2 – Zero Hunger (indirect) (Value addition to local cassava resources)